2004
DOI: 10.1212/01.wnl.0000147261.22630.f8
|View full text |Cite
|
Sign up to set email alerts
|

Strokes in the subinsular territory

Abstract: The authors studied 11 patients with subinsular stroke (subIS) located in a deep border zone between lenticulostriate arteries and small insular cortical penetrating branches of the middle cerebral artery. The typical clinical features of subIS were motor deficits (11 patients), sensory disturbances (6 patients), transcortical motor aphasia and hypophonia (2 patients), and transient dysphagia at stroke onset (5 patients). Large artery disease and cardioembolic mechanisms may give rise to subIS by hemodynamic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Changes in cardiac rhythm have been demonstrated in association with electrical stimulation of the insular and temporal cortices by other investigators (18,44). It should be noted that not all investigators have been able to demonstrate cardiovascular effects in response to disturbances of function in the temporal lobe and insula (58–60).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in cardiac rhythm have been demonstrated in association with electrical stimulation of the insular and temporal cortices by other investigators (18,44). It should be noted that not all investigators have been able to demonstrate cardiovascular effects in response to disturbances of function in the temporal lobe and insula (58–60).…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial perforating arteries and small branches of the circle of Willis provide blood supply to the brain stem and deep grey and white matter structures of the brain [1, 2]. Acute occlusion of these perforating arteries may cause infarctions with profound clinical symptoms, while chronic small vessel disease of the perforating arteries may cause chronic white matter lesions in the pons and the cerebrum [37].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic ischemic brain injury is known to lead to mental retardation and deficits in cognitive abilities, such as learning and memory. Impairment of the performance of hypoxic ischemic rats in a water maze task was unlikely to be due to changes in motivation, sensorimotor function, or visual impairment (Kumral et al 2004). A previous study suggested that impairment of performance in hypoxic ischemia rats was due to learning and memory deficits (Anderson and Arciniegas 2010).…”
Section: Discussionmentioning
confidence: 91%